Effects of knee flexion angle manipulation on impact loading and metabolic costs during running - Clansey, A.; Hassan, E.; Selbie, S.; Brown, M.; Shew, J.; Deluzio, K. (International Calgary Running Symposium, August 14-17, 2014, 2014)
There is a strong association with greater loading rates and overuse injury risk in runners (Zadpoor and Nikooyan, 2011). The position of the knee joint relative to the center of pressure at contact is known to play an important role in influencing vertical ground reaction forces (vGRF) and metabolic costs during running. Running with an increased knee flexion at initial contact may, therefore, reduce injury risk. The purpose of this investigation was to examine the relationship between knee flexion angle at contact, impact loading rate, and metabolic cost during running. Twelve recreational runners (27.2 ±7.2 y; 68.3 ±8.9 kg; 1.8 ±0.1 m) performed 3 x 5 min run conditions at a self-selected speed (3.19 ±0.45 m/s). In each condition subjects ran with different knee angles at contact. The conditions were controlled by providing the subjects with graphical biofeedback of the knee angle at contact of the previous stride(s) and instructed to maintain the knee angle within a prescribed range of angles (10-20°, 20-30° or 30-40°). Synchronized motion and force data were collected at 250 Hz and 1250 Hz during the last 30 s of each run. Metabolic data was collected during the entire 5 minutes of each condition. Progressive increases in knee flexion at contact significantly reduce loading rates but with an increased VO2 uptake (Fig 1.). All runners were able comfortably modify their loading rates based on the biofeedback but this came with an increased metabolic cost which is consistent with groucho style running (McMahon et al., 1987).